Structured student-generated videos for first-year students at a Dental School in Malaysia - Omar, H.; Khan, S.A.; Toh, C.G. (American Dental Education Association, 2012)

(untitled)
Student-generated videos provide an authentic learning experience for students, enhance motivation and engagement, improve communication skills, and improve collaborative learning skills. This article describes the development and implementation of a student-generated video activity as part of a knowledge, observation, simulation, and experience (KOSE) program at the School of Dentistry, International Medical University, Kuala Lumpur, Malaysia. It also reports the students' perceptions of an activity that introduced first-year dental students (n=44) to clinical scenarios involving patients and dental team aiming to improve professional behavior and communication skills The learning activity was divided into three phases: preparatory phase, video production phase, and video-watching. Students were organized into five groups and were instructed to generate videos addressing given clinical scenarios. Following the activity, students' perceptions were assessed with a questionnaire. The results showed that 86 percent and 88 percent, respectively, of the students agreed that preparation of the activity enhanced their understanding of the role of dentists in provision of health care and the role of enhanced teamwork. In addition, 86 percent and 75 percent, respectively, agreed that the activity improved their communication and project management skills. Overall, the dental students perceived that the student-generated video activity was a positive experience and enabled them to play the major role in driving their learning process.